1987
DOI: 10.1002/1097-0142(19871101)60:9<2237::aid-cncr2820600923>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine decarboxylase activity, prolactin blood levels, and estradiol and progesterone receptors in human breast cancer

Abstract: Ornithine decarboxylase (ODC) activity in human breast cancer tissues was correlated with prolactinemia (Prl), estradiol and progesterone cytosol receptors (ER and PR), and histopathologic pattern. Ninety-two cases of breast cancer, six benign mammary disease, and three normal breast tissues were studied for ER, PR, and ODC. Prolactinemia was assessed in 59 cancer patients, 14 of whom showed hyper-Prl along with significantly higher O X than in patients with normal-Prl I(20.01 & 6.33) lo-' YS (5.20 k 0.90) lo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…7). Of clinical relevance, increased ODC activity in primary tumors has been found to be associated with adverse prognostic features (8,9). More importantly, we (10) and subsequently other investigators (9) have shown that high tumor ODC activity is an independent, adverse prognostic factor for disease-free and overall survival in patients with localized breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Of clinical relevance, increased ODC activity in primary tumors has been found to be associated with adverse prognostic features (8,9). More importantly, we (10) and subsequently other investigators (9) have shown that high tumor ODC activity is an independent, adverse prognostic factor for disease-free and overall survival in patients with localized breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among the multiple effects of DFMO we have shown that induction of MAPK activation is instrumental in its antiinvasive action since the anti-invasive effects of the drug could be reversed with the MEK inhibitor PD98059 (5). Furthermore, we have shown that DFMO-induced MAPK activation is causally linked to upregulation of TSP-1 (5), an extracellular matrix glycoprotein with tumor suppressive and antimetastatic activity primarily resulting from its potent anti-angiogenic effect (6)(7)(8)(9). Because of its possible role as mediator of the anti-metastatic effect of DFMO in breast cancer, we deemed it important to investigate the mechanisms of regulation of TSP-1 production by DFMO under both in vitro and in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Using an experimental system of mammary tumor progression, we found that an increase in cellular ODC activity was associated with transition to hormone independence as well as to a less differentiated and more metastatic phenotype [52]. With respect to human breast cancer, increased ODC activity has been shown to be associated with adverse prognostic features such as high cellularity, low histological differentiation, high nuclear aplasia, peritumoral lymphatic and blood vessel invasion, high S-phase fraction, and cathepsin-D expression [15,53]. In a pilot study involving a cohort of 50 primary human breast cancers, we have observed that ODC activity was a strong negative independent prognostic factor of overall survival [54].…”
Section: Polyamines and Tumor Progressionmentioning
confidence: 99%
“…ODC becomes activated after treatment with chemical carcinogens and tumor promoters, as well as in cells transformed by various oncogenes such as v-src, neu and ras. [6][7][8] The level of ODC was reportedly elevated in various cancers [9][10][11] and related to recurrence. 12 Some chemotherapeutic agents, such as DFMO, which aimed to inhibit the activity of ODC have appeared and taken on inhibitory effects on tumor growth in vitro and in vivo, 13,14 although showing dose-limiting toxicity.…”
Section: Introductionmentioning
confidence: 99%